Celiac disease in children: Increasing prevalence and changing clinical presentations - Hasan M. Isa; Eman Farid; Jaafar J. Makhlooq; Afaf M. Mohamed; Jumana G. Al-Arayedh; Fawzeya A. Alahmed; Shima Medani (The Korean Pediatric Society, 2021)
Background Celiac disease (CD) is a chronic autoimmune enteropathy. It results from genetic predisposition and exposure to gluten-containing food. The prevalence and presentation of CD vary among populations. Purpose This study aimed to describe the prevalence and clinical characteristics of CD in children in Bahrain. Methods We retrospectively reviewed the medical records of children diagnosed with CD in the pediatric department, Salmaniya Medical Complex, Bahrain, in 1988-2018. Their clinical, biochemical, serological, and histopathological findings were documented. Adherence to the recommended gluten-free diet (GFD) was assessed. Results Of 86 patients with CD, 67 were included. The CD prevalence was 0.02%. A significant increase in prevalence in the last decade was observed (P<0.0001). Thirty-eight patients (56.7%) were males. The median (interquartile range) age at presentation was 4.45 (1.5-7.3) years. A family history of CD was positive in 13 out of 43 patients (30.2%). Pallor and failure to thrive were the most common presentations. The most frequent associated disease was iron-deficiency anemia in 23 patients (69.7%). Positive serology was found in 32 of 45 patients (71.1%). Marsh-Oberhuber type III was found in 16 of 35 patients (45.7%). Seropositive patients were significantly older (P=0.025) and had more severe duodenal histology (P=0.002). Adherence to GFD was poor in 27 patients (64.3%). Conclusion This study revealed a significant increase in CD prevalence over the last decade. Atypical presentations were frequent. Most patients had poor adherence to GFD.